Dynamic pollution model - Khrapko, V.N. (Культура народов Причерноморья, 2001)
The goal of the work is a macroeconomics modeling of ecological problems, more exactly, problem of industrial pollution and cleaning with special technologies. This problem is actual one especially if to take into consideration current caloric pollution.